Semiotics of Kafeena: Integration of Verbal and Nonverbal Symbolic Communication in The Wedding Ritual of The Muna Tribe - Irna Purnama Sari (MUKASI: Jurnal Ilmu Komunikasi, 2026)
This study examines symbolic communication in the Kafeena (pinangan) tradition at the wedding of the Muna tribe in Wali Village, Watuputih District, Muna Regency. The background of this study is the lack of understanding of the community, especially the younger generation, regarding the meaning of verbal and nonverbal communication in the Kafeena procession, which has caused the erosion of local cultural values. This study aims to reveal the symbolic meaning contained in the verbal and nonverbal elements of Kafeena, as well as to provide cultural education as an effort to preserve traditional heritage. The method used is descriptive qualitative with data collection techniques through observation, interviews, documentation, and literature studies. Roland Barthes' semiotic theory is used as an analytical tool s to unravel the denotative and connotative meanings of the symbols in the proposal procession. The results of the study show that Kafeena contains spiritual, social, and cultural meanings conveyed through traditional questions in the form of amenakomu ini and abhentamo pongke ini as well as symbolic objects such as rings, the Qur'an, bathing equipment, and other objects. These findings confirm that Kafeena is a complex cultural communication medium. The conclusion of this study shows that understanding symbolic communication in Kafeena is important to be maintained and passed on through cross-generational education programs to strengthen the cultural identity of the Muna tribe in facing the current of modernization.